Storm Surges and Extreme Wind Waves in the Caspian Sea in the Present and Future Climate - Anna Pavlova; Stanislav Myslenkov; Victor Arkhipkin; Galina Surkova (Civil Engineering Journal, 2022)
The Caspian Sea is of particular interest. Against the background of long-term sea level changes, low-lying coastal areas in the northern part are subject to constant flooding as a result of storm surges. The elongation of the sea in the meridional direction allows the development of strong waves in the middle and southern parts. A comprehensive understanding of the characteristics of storm surges and storm waves is especially important in the context of ongoing climate change. This study is devoted to the analysis of storm surges for the time period from 1979 up to 2017 and wind waves from 1979 to 2020 in the Caspian Sea region. The circulation model ADCIRC and the wave model WAVEWATCH III with wind and pressure forcing from the NCEP/CFSR reanalysis were used. The modeling is performed on different unstructured grids with spacings of 500–900 m in the coastal zone. Mean and extreme values of surges, wave parameters and storm activity are provided in the research. The maximum significant wave height for the whole period was 8.2 m. The average long-term SWH did not exceed 1.1 m. No significant trends in the storm activity were found. The maximum surge height was 2.7 m. The analysis of the interannual variability of the surges' occurrence showed that 7–10 surges with a height of more than 1 meter were detected every year. The total duration of these surges was 20–30 days per year. Assessment of the risks of coastal flooding was carried out by calculating the extreme values of the sea for different return periods: 5, 10, 25, 50, and 100 years. The extreme sea level values in the northern part of the Caspian Sea for the 100-year return period are close to 3 m, and the areas with big surges are located along the eastern and western coasts. A forecast is made for the recurrence of storm wind waves in the 21st century based on climatic scenarios in CMIP5. A statistically significant increase in the recurrence of storm waves is to be expected in the near future, but that increase is not severe. Doi: 10.28991/CEJ-2022-08-11-01 Full Text: PDF